Combined effects of ambient temperature and food availability on induced innate immune response of a fruit-eating bat (Carollia perspicillata) - Viola, Matheus F. [UNESP]; Herrera, L.M. Gerardo; Cruz-Neto, Ariovaldo P. [UNESP] (Public Library of Science (PLoS), 2024)
Resilience of mammals to anthropogenic climate and land-use changes is associated with the maintenance of adequate responses of several fitness-related traits such as those related to immune functions. Isolated and combined effects of decreased food availability and increased ambient temperature can lead to immunosuppression and greater susceptibility to disease. Our study tested the general hypothesis that decreased food availability, increased ambient temperature and the combined effect of both factors would affect selected physiological and behavioral components associated with the innate immune system of fruit-eating bats (Carollia perspicillata). Physiological (fever, leukocytosis and neutrophil/lymphocyte ratio) and behavioral (food intake) components of the acute phase response, as well as bacterial killing ability of the plasma were assessed after immune challenge with lipopolysaccharide (LPS: 10 mg/kg) in experimental groups kept at different short-term conditions of food availability (ad libitum diet or 50% food-deprived) and ambient temperature (27 and 33oC). Our results indicate that magnitude of increase in body temperature was not affected by food availability, ambient temperature or the interaction of both factors, but the time to reach the highest increase took longer in LPS-injected bats that were kept under food restriction. The magnitude of increased neutrophil/lymphocyte ratio was affected by the interaction between food availability and ambient temperature, but food intake, total white blood cell count and bacterial killing ability were not affected by any factor or interaction. Overall, our results suggest that bacterial killing ability and most components of acute phase response examined are not affected by short-term changes in food availability and ambient temperature within the range evaluated in this study, and that the increase of the neutrophil/lymphocyte ratio when bats are exposed to low food availability and high ambient temperature might represent an enhancement of cellular response to deal with infection.